2010
DOI: 10.1074/jbc.m109.088674
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived Growth Factor Differentially Regulates the Expression and Post-translational Modification of Versican by Arterial Smooth Muscle Cells through Distinct Protein Kinase C and Extracellular Signal-regulated Kinase Pathways

Abstract: The synthesis of proteoglycans involves steps that regulate both protein and glycosaminoglycan (GAG) synthesis, but it is unclear whether these two pathways are regulated by the same or different signaling pathways. We therefore investigated signaling pathways involved in platelet-derived growth factor (PDGF)-mediated increases in versican core protein and GAG chain synthesis in arterial smooth muscle cells (ASMCs). PDGF treatment of ASMCs resulted in increased versican core protein synthesis and elongation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 47 publications
(51 reference statements)
0
30
0
Order By: Relevance
“…GAG chain hyperelongation occurs by growth factor stimulation of the expression of the GAG chain synthesizing enzymes in vascular smooth muscle cells (VSMCs) Ivey and Little, 2008;Yang et al, 2009;Burch et al, 2010;Cardoso et al, 2010;Yang et al, 2010;Osman et al, 2014). Prevention of this change in proteoglycan structure by targeting the hormone and growth factor signalling pathways has been proposed and demonstrated as a therapeutic target to prevent atherosclerosis (Ballinger et al, 2004;Little et al, 2007;Osman et al, 2008;Little et al, 2011); the signalling pathways are the preferred target because these pathways are specific for VSMCs which is not the case for the action of the elongation enzymes themselves which are ubiquitously expressed and functional in most tissues of the body.…”
Section: Introductionmentioning
confidence: 99%
“…GAG chain hyperelongation occurs by growth factor stimulation of the expression of the GAG chain synthesizing enzymes in vascular smooth muscle cells (VSMCs) Ivey and Little, 2008;Yang et al, 2009;Burch et al, 2010;Cardoso et al, 2010;Yang et al, 2010;Osman et al, 2014). Prevention of this change in proteoglycan structure by targeting the hormone and growth factor signalling pathways has been proposed and demonstrated as a therapeutic target to prevent atherosclerosis (Ballinger et al, 2004;Little et al, 2007;Osman et al, 2008;Little et al, 2011); the signalling pathways are the preferred target because these pathways are specific for VSMCs which is not the case for the action of the elongation enzymes themselves which are ubiquitously expressed and functional in most tissues of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Because platelet accumulation is indeed important in the genesis of restenosis, we reasoned that the extra cellular matrix protein denatured under beta-radiation might help reduce the onset of acute coronary events and of in the genesis of restenosis. In addition, the growth factor released by activated platelet, stimulated the proliferation of smooth muscle cells, which may be an influential factor in the restenosis [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, if cells are supplemented with exogenous xyloside then the xyloside acts as a "false acceptor" for subsequent residues and the synthesis of free GAG chains (xyloside GAGs) occurs, albeit generating short GAG chains relative to those synthesized on core proteins [28]. The synthesis of xyloside GAGs serves as a cellular assay for GAG synthesizing capacity and we have previously reported that this process responds to growth factors and inhibitors [28,[40][41][42]. We grew ASMCs to confluency, serum-deprived the cells for 24 h then provided the cells with exogenous xyloside (0.5 mM) and [ 35 S]-sulfate for a further 24 h. We harvested the media, isolated the radiolabelled PGs and xyloside GAGs by CPC precipitation and DEAE-sephacel ion exchange chromatography then subjected the xyloside GAGs to size analysis using a 20% SDS-PAGE.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these enzymes work in pairs to affect monosaccharide addition and GAG elongation or otherwise sulfation and some can contribute to GAG elongation in the absence of their transferase activities [17]; in practice these enzymes are only capable of synthesizing relatively short GAG chains in vitro. Thus, some of these enzymes, notably chondroitin 4-O-sulfotransferase-1 (C4ST-1) and chondroitin N-acetylgalactosaminyltransferase-2 (ChGn-2), are involved in GAG synthesis [33] and we speculate that the increased expression of one or more of these enzymes mediates the hyperelongation response to growth factors such as TGF-β, PDGF and GPCR agonists such as thrombin and endothelin [22,25,26,40]. Thus we can speculate that ASMCs from the aorta of ApoE -/-compared to those prepared from their control ApoE +/+ mice strain have a higher level of expression of one or more GAG synthesizing enzymes such that the capacity to synthesize GAGs in the Golgi is enhanced and biglycan with longer GAG chains is synthesized and secreted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation